STUDI NORMATIF ANTI TESA PEMIKIRAN HUKUM SYARIAH TERHADAP PEMIKIRAN MAZHAB HUKUM ALAM - Muhammad Sjaiful (Al-Maslahah : Jurnal Ilmu Syariah, 2015)
The idea of natural law school of thought, has been the notion that almost influence the thinking of the legal scholars who had studied law in several law schools in Indonesia. Even the idea of natural law school of thought is one of the thematic that must be studied by law students who take courses in legal philosophy major. It is tempting on the substance of the natural law school of thought is the topic of conversation on the law as something that is transcendental (apocalyptic) that should not be separated from morality and justice. Apocalyptic characteristics of the basic core of natural law school of thought ultimately became a reference for Muslim intellectual who studied the philosophy of Islamic law, with the conclusion that this idea is very compatible with the thought of sharia law. It is unfortunate presumption thought so, because the law school of the true nature of the natural birth of Ancient Greek thought is the basis of western civilization milestones, will be different with the thinking that upholds sharia law Islamic faith. To that end, the purpose of this paper is to conduct a thorough analysis of the difference between thinking sharia law and natural law school of thought.